2013
DOI: 10.1002/asia.201300122
|View full text |Cite
|
Sign up to set email alerts
|

Could Carbonaceous Impurities in Reduced Graphenes be Responsible for Some of Their Extraordinary Electrocatalytic Activities?

Abstract: Thermally and chemically reduced graphene materials contain significant amounts of carbonaceous impurities that are similar in structure to amorphous carbon. Herein, we show that the claimed electrocatalytic activities of these materials for the oxidation of NADH, acetaminophen, and hydroquinone are mainly due to the presence of carbonaceous impurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In addition to metallic impurities, carbonaceous impurities in GN were also reported to significantly impact its electrochemical performance 180. 207, 214 For example, after the removal of the carbonaceous oxidative impurities from GN,207 the specific capacitance of purified GN is lower than that of unpurified GN (GN was prepared by GO electroreduction215 and GO was synthesized by Hummers’ method)208 but similar to that of pure GN 216. It was implied that the presence of the carbonaceous impurities might increase the wettability and prevent the risk of restacking of GN sheets if they were deposited on the electrode surface, and so that the increased surface area of GN thus enhanced the charge adsorption on the surface of GN and improve its capacitor performance 207…”
Section: Advanced Electrochemical Sensors Based On Graphene (Gn)mentioning
confidence: 99%
“…In addition to metallic impurities, carbonaceous impurities in GN were also reported to significantly impact its electrochemical performance 180. 207, 214 For example, after the removal of the carbonaceous oxidative impurities from GN,207 the specific capacitance of purified GN is lower than that of unpurified GN (GN was prepared by GO electroreduction215 and GO was synthesized by Hummers’ method)208 but similar to that of pure GN 216. It was implied that the presence of the carbonaceous impurities might increase the wettability and prevent the risk of restacking of GN sheets if they were deposited on the electrode surface, and so that the increased surface area of GN thus enhanced the charge adsorption on the surface of GN and improve its capacitor performance 207…”
Section: Advanced Electrochemical Sensors Based On Graphene (Gn)mentioning
confidence: 99%
“…Several authors have studied the effect of CF on the electrochemical performance of CNT and graphene materials . The presence of CF was reported to have a positive effect on the electrochemical oxidation of β‐nicotinamide adenine dinucleotide (NADH) and ascorbic acid (AA) at a glassy carbon electrode coated with CNT .…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Several authors have studied the effect of CF on the electrochemicalp erformance of CNT and graphene materials. [32][33][34][35][36][37][38][39] The presence of CF was reportedt oh ave ap ositive effect on the electrochemical oxidation of b-nicotinamide adenine dinucleotide (NADH) and ascorbic acid (AA) at ag lassy carbon electrode coated with CNT. [32] Conversely,t he oxidation of NADH mediated by 1,10-phenantroline-5,6-dione wasa dversely influenced by the presence of CF on the GO surface.…”
Section: Introductionmentioning
confidence: 99%
“…Pumera’s group has demonstrated before that single‐, few‐, and multilayer graphenes do not exhibit significant advantages over graphite microparticles in connection with the measurement of ascorbic acid and uric acid 27. They further pointed out that the carbonaceous impurities in the form of amorphous carbon within graphene samples were responsible for the observed electrocatalytic effects of the graphene surfaces towards important compounds, such as NADH, hydroquinone, and acetaminophen 28. Recently, the group has revealed that residual metal impurities (Fe, Co, and Ni) present in graphene are responsible for the electrocatalytic properties towards several molecular probes, such as NaSH, l‐glutathione, cumene hydroperoxide, and hydrazine 29.…”
mentioning
confidence: 99%
“…[27] They further pointedo ut that the carbonaceous impurities in the form of amorphous carbon within graphene samplesw erer esponsible for the observed electrocatalytic effects of the graphenes urfaces towardsi mportant compounds, such as NADH, hydroquinone, and acetaminophen. [28] Recently, the group has revealed that residualm etal impurities (Fe, Co, andN i) present in graphene are responsible for the electrocatalytic properties towardss everalm olecular probes, such as NaSH,l -glutathione, cumene hydroperoxide, and hydrazine. [29] These discoveries suggest that the electrocatalysiso fg raphenem ay be induced by heterogeneous substances present in graphene sheets rathert han graphene itself.…”
mentioning
confidence: 99%